2011
DOI: 10.1007/s11292-011-9130-z
|View full text |Cite
|
Sign up to set email alerts
|

The possible “backfire” effects of hot spots policing: an experimental assessment of impacts on legitimacy, fear and collective efficacy

Abstract: Objectives To examine the impacts of broken windows policing at crime hot spots on fear of crime, ratings of police legitimacy and reports of collective efficacy among residents of targeted hot spots. Methods A block randomized experimental design with a police intervention targeting disorder delivered to 55 treatment street segments with an equal number of segments serving as controls. Main outcomes were measured using a panel survey of 371 persons living or working in these sites. Results The broken windows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 37 publications
2
125
0
Order By: Relevance
“…Prior studies have found mixed support for the notion that perceived police (in)effectiveness either diminishes or heightens fear of crime (Hinkle & Weisburd, 2008;Silver & Miller, 2004;Weisburd, Hinkle, Famega, & Ready, 2011;Zhao et al, 2002). Order maintenance policing, in particular, has met with mixed results in terms of fear reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found mixed support for the notion that perceived police (in)effectiveness either diminishes or heightens fear of crime (Hinkle & Weisburd, 2008;Silver & Miller, 2004;Weisburd, Hinkle, Famega, & Ready, 2011;Zhao et al, 2002). Order maintenance policing, in particular, has met with mixed results in terms of fear reduction.…”
Section: Discussionmentioning
confidence: 99%
“…While some recent studies continue to reaffirm Sherman and Weisburd's (1995) original finding, that the saturated police presence at hotspots reduces crime and disorder (Telep et al 2014a, b), others have begun to look more closely at precisely what type of police presence prevents crime. For example, some have looked at problem-oriented policing (Weisburd and Green 1995;Braga et al 1999;Braga and Bond 2008;Taylor et al 2011); drug enforcement operations (Weisburd andGreen 1994, 1995); increased gun searches and seizures (Sherman and Rogan 1995); foot patrol (Ratcliffe et al 2011); crackdowns (Sherman and Rogan 1995); 'zero-tolerance' policing or 'broken windows tactics' (Caeti 1999;Weisburd et al 2011); 'soft policing' (Ariel et al 2016); and intensified engagement (Rosenfeld et al, 2014). Despite these treatment variations, there are nevertheless common attributes to all hotspots policing approaches.…”
Section: Policing Hotspots Of Crime and Disordermentioning
confidence: 99%
“…Yet others have begun to look more closely at precisely what specific aspects of police presence may more effectively prevent crime than others. For example, some have looked at problem-oriented policing (e.g., Braga and Bond 2008;Braga et al 1999;Taylor et al 2010;Weisburd and Green 1995), drug enforcement operations (e.g., Weisburd andGreen 1994, 1995), increased gun searches and seizures (e.g., Sherman and Rogan 1995a, b), foot patrols (e.g., Ratcliffe et al 2011), crackdowns (Sherman and Rogan 1995a), Bzero-tolerancep olicing or Bbroken windows tactics^ (Caeti 1999;Weisburd et al 2011), and intensified engagement (Rosenfeld et al 2014). Yet few of these studies provide detailed measures of exactly what police were doing in the experimental hot spots; even one that did (Sherman and Rogan 1995a, b) failed to measure what police did in the control hot spot.…”
Section: Introductionmentioning
confidence: 99%